Association between Alzheimer’s Disease and Apolipoprotein E Polymorphisms - E Gozalpour (Iranian Journal of Public Health, 2010)
Background: Alzheimer's disease as a neurodegenerative disorder is the commonest type of dementia. A growing number of genes have been reported as the risk factors, which increase the susceptibility to Alzheimer's disease. Apolipoprotein E (APOE), which its ε4 allele has been reported as a risk factor in late onset Alzheimer's disease (AD), is the main cholesterol carrier in the brain. The main goal of this study was to assess the role of APOE genotypes and alleles in AD in Iranian population. Methods: This study was performed in Tehran, Iran from 2007 to 2008. Totally, 154 AD cases and 162 control subjects from Iranian population were genotyped for APOE using PCR method. Genotype and alleles frequencies for APOE were calculated and compared between AD case and control subjects by χ2 or Fisher's exact test. Type one error assumed less than 0.05. Results: The frequency of ε2ε3 genotype was significantly higher in control subjects than AD patients was (13.5% versus 5.2%, P< 0.05) and ε3ε4 genotype frequency was significantly higher in AD cases compared with control subjects. APOE -ε2 allele frequency in cases was lower than that of control subjects but this difference was not significant (4.2% versus 7.7%). Conclusion: It seems that individuals carrying ε4 allele, develop AD 6.5 times more than non-carriers do (OR= 6.566, 95% CI= 2.89-14.92). It has been reported that ε4 allele acts in dose- age-dependent manner but we have shown that the risk of developing AD in male APOE -ε4 allele carriers is higher than that of female ε4 carriers.